Drought Effects on Physiology and Biochemistry of Pedunculate Oak (Quercus robur L.) and Hornbeam (Carpinus betulus L.) Saplings Grown in Urban Area of Novi Sad, Serbia - Srđan Stojnić; Saša Pekeč; Marko Kebert; Andrej Pilipović; Dejan Stojanović; Marko Stojanović; Saša Orlović (South-East European Forestry, 2016)
Background and Purpose: Water stress is one of the major problems for urban trees. It affects a wide range of plant responses, from changes at the cellular level to the reduction in growth rates. Irrigation of trees in urban areas may provide numerous benefits important for increasing tree vitality to withstand other stresses that might occur. The aim of this study was to compare drought effects on some physiological and biochemical performances of Pedunculate oak (Quercus robur L.) and Hornbeam (Carpinus betulus L.) saplings grown in the urban area. Materials and Methods: The study was conducted during August 2012 at the Boulevard of Europe (Novi Sad, Republic of Serbia). Measurements were carried out on saplings grown in the part of the boulevard with drip irrigation system installed (Site 1) and on the saplings cultivated in the part without any irrigation system (Site 2). Results: Soil moisture content was significantly higher at Site 1 with approximately 57.2%, compared to 18.7% at Site 2. The results showed that irrigated saplings were characterized by significantly higher stomatal conductance in Q. robur and C. betulus. Similarly, the content of free proline, FRAP units and the amount of malonyldialdehyde showed increased values in trees subjected to soil water deficit. In contrast, net photosynthesis, chlorophyll and carotenoid contents did not differ notably in irrigated and non-irrigated Q. robur and C. betulus trees. Conclusions: Water stress significantly affected stomatal conductance and some biochemical properties of Q. robur and C. betulus saplings cultivated at the non-irrigated site. The results showed that the implementation of drip irrigation system in urban landscape is an important tool in the prevention of drought stress effects on the physiological processes of plants.